Assessing the scenic views in the hedonic modelling of residental property prices - Tan, Yu Tian, 1987-; Abdul Hamid Mar Iman; Fakulti Geoinformasi dan Harta Tanah (2011)
Project Paper (Sarjana Muda Sains (Pengurusan Harta Tanah)) - Universiti Teknologi Malaysia, 2011